Investigation On Vision Lead Over Rejection For D-PAK Package At Testing Operation Using Seven Quality Control Tools - Semposothy, Sevasothy (2017)
In semiconductor industries, it as a common problem for the manufacture to falsely reject good product, part or component in their production lines due to error measurement of their vision inspection system. This scenario is very costly to the manufacturers in term of cycle time, scrap and delivery time. As a matter of fact, this problem can affect the credulity of the manufacturer from the customer’s perspective. Therefore, this project attempt to investigate the root cause of the falsely reject products which is known as over rejection for a semiconductor’s manufacturer in Melaka. Specifically, this project looked at over rejection for a lead to a integrated circuit device. Through this research, the root cause of the over rejection that are spring back soft 3D vision pedestal material, worn out pickup head and dirty 3D vision system mirror have been identified using Seven Quality Control tools. Counter measure to overcome those issues that are replacing vision pedestal material with a harder material, introduce the use of jig and clean the vision mirror using elastic or bended cotton stick have been implemented to reduce or eliminate the above mentioned problem. After implementing the counter measure, over rejection due to soft vision pedestal material has been totally eliminated. Whereas, the problem due to worn out pickup head and dirty vision system mirror have been significantly reduced to 65.7% and 61.5% respectively. In fact the vision lead reject has been tremendously declined from being top 13 to the top 2 the lowest reject in overall reject detected at testing operation of the production line.